A pilot study to determine the consistency of peak forces during cervical spine manipulation utilizing mannequins - Duquette, Sean A. (J Chiropr Educ, 2020)
OBJECTIVE: Cervical spine manipulation is a complex motor skill used to treat musculoskeletal ailments such as neck pain. There is evidence demonstrating the effectiveness of objective feedback and mannequins for the teaching of spinal manipulation (SM) in the thoracic and lumbar spine. This paper examines the effectiveness of an educational intervention combining both mannequins and force-sensing technology for teaching cervical SM. METHODS: Fourth-year chiropractic interns were separated into 2 groups: an intervention group and a group trained with the standard curriculum. The intervention included a 60-minute educational session focused on targeting 100 N total peak force cervical manipulations on mannequins, with objective feedback through force-sensing table technology. Pre- and post-CMs were recorded on both a mannequin and a paired student partner, with an attempt to have a target total peak force of 100 N. RESULTS: Ninety students were recruited. The invention group (n = 46) scored significantly better at the outcome compared to the control group (n = 44) when manipulating the mannequin (p = .003). These improvements did not carry over when manipulating a paired human partner (p = .067). CONCLUSION: Following a 1-hour cervical SM educational intervention utilizing thrusting on mannequins and force-sensing table technology, students demonstrated improved peak force control for SM delivered on the mannequin. However, this improvement was not carried over to SM delivered on human subjects.